Factors Influencing the Quality of Life of Undergraduate Students, Uttaradit Rajabhat University - Thanasupawat, Boonmun; Sooksa, Withaya; Wanthong, Samniang; Maprakhob, Sutapa (MCU Haripunchai Review, 2026)
The research results revealed that 1) the level of factors influencing the quality of life of undergraduate students; 2) the level of quality of life of students; 3) factors predicting the quality of life of students; and 4) guidelines for enhancing the quality of life of undergraduate students at Uttaradit Rajabhat University.The sample group consisted of 371 undergraduate students in their 1st-4th years during the first semester of the 2025 academic year. A purposive sampling method was used, calculated using Taro Yamane’s formula. The research instruments included a quality of life measurement scale and questionnaires. Data were analyzed using statistical software. Statistical methods employed included percentages, means, standard deviations, and multiple regression analysis. The research findings revealed that: 1) All factors had a significant overall influence on the quality of life ofstudents. Ranked from highest to lowest mean, the factors were: family, physical health, expenses, education, and mental health, social relationships and the environment, respectively, were the most important factors in determining students’ quality of life. 2) The majority of students (51.48%) had a moderate quality of life, followed by 45.55% with a good quality of life and 2.97% with a poor quality of life. 3) All factors together significantly predicted 50.69% of the variance in students’ quality of life at the 0.01 significance level. 4) The top three approaches to enhancing students’ quality of life, in order of frequency, were: 1) Openness to learning new skills or knowledge that are beneficial to life and work; 2) Adaptability to any situation for a better quality of life; and 3) Building good relationships with others and participating in various social activities.